2014
DOI: 10.1111/ajt.12866
|View full text |Cite
|
Sign up to set email alerts
|

Early Corticosteroid Avoidance in Kidney Transplant Recipients Receiving ATG-F Induction: 5-Year Actual Results of a Prospective and Randomized Study

Abstract: One hundred ninety-seven patients received anti-Tlymphocyte globulins Fresenius, mycophenolate mofetil and delayed cyclosporine, and were randomized to !6-month corticosteroids (þCS; n ¼ 99) or no CS (ÀCS; n ¼ 98). One-and five-year actual graft survival (censored for death) was 93.2% and 86.4% in the þCS group versus 94.9% and 89.8% in the ÀCS group (5-year follow-up, p ¼ 0.487). Freedom from clinical rejection was 86.9% and 81.8% versus 74.5% and 74.5% (p ¼ 0.144), respectively, at 1 and 5 years; 5-year free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 40 publications
(47 reference statements)
0
21
0
Order By: Relevance
“…There is a long history of steroid avoidance or withdrawal in transplantation . Most practitioners still consider prednisolone to be a fundamental adjunct to primary immunosuppression, even though successful prednisolone withdrawal has been achieved in the vast majority of patients in many prospective, randomized trials .…”
Section: Current Strategies Of Immunosuppression Minimizationmentioning
confidence: 99%
“…There is a long history of steroid avoidance or withdrawal in transplantation . Most practitioners still consider prednisolone to be a fundamental adjunct to primary immunosuppression, even though successful prednisolone withdrawal has been achieved in the vast majority of patients in many prospective, randomized trials .…”
Section: Current Strategies Of Immunosuppression Minimizationmentioning
confidence: 99%
“…Two prospective randomized studies comparing RDP with maintenance prednisone found no significant difference in patient survival, graft survival, or renal function at 5 years post‐transplant. In a single‐center analysis of 1st and 2nd transplant recipients, we found no difference in 15‐year patient or graft survival between those on RDP and those on maintenance prednisone . In a subanalysis of that study, we compared recipients with at least 5‐year graft survival on RDP ( n = 859) versus maintenance prednisone ( n = 317) and found no difference between groups in patient or graft survival between 5 and 15 years post‐transplant.…”
Section: Discussionmentioning
confidence: 88%
“…When first introduced, RDP was shown to have similar short‐term patient and graft survival rates, as compared with maintenance prednisone; however, concern remained that RDP would be associated with increased rates of late deterioration of kidney graft function and graft loss. But to date, no study, review, or meta‐analysis has reported decreased rates of long‐term patient and/or graft survival with RDP . Two prospective randomized studies comparing RDP with maintenance prednisone found no significant difference in patient survival, graft survival, or renal function at 5 years post‐transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, however, protocols discontinuing steroids within the first postransplant week (under cover of depletional induction and full dosing of other immunosuppressives) have had better success-slightly more acute rejection, but no decrement in 5-year patient and graft survival, with fewer steroid-related side effects. [5][6][7] The introduction of calcineurin inhibitors (CNIs) resulted in less acute rejection, but concerns regarding long-term nephrotoxicity and other CNI-specific side effects 8 led quickly to trials of CNI minimization. Similar to the previous approaches with corticosteroids, CNI-minimization and avoidance trials enrolled cohorts either from the entire transplant population or preselected subgroups thought to be at low immunologic risk.…”
mentioning
confidence: 99%